PENGEMBANGAN MEDIA KOMIK SAKU (KOMIKU) PENGETAHUAN PENCEGAHAN KARIES GIGI PADA ANAK SEKOLAH DASAR KECAMATAN CIMAHI TENGAH (Jurnal Kesehatan Siliwangi, 2023)
Background: Maintaining dental and oral health must be instilled early in order to avoid problems that are often experienced by children during their dental growth, one of which is dental caries. Efforts made as a health promoter are to provide health education about the prevention of dental caries in children using media. The development of pocket comics media (komiku) on the prevention of dental caries is one of the innovations in providing education that makes it easier for children to learn. Objective: to see and assess the pocket comic media (komiku) for the prevention of dental caries in children. Methods: The research was conducted using research and development R&D (Reseach and Development) with the ADDIE development model, namely Analysis, Design, Development, Implement, and Evaluation. The number of samples was 38 students with a technique approaching the sample using a total sampling technique. Types and methods of data collection using questionnaires given to experts and users in certain media. The data analysis technique used descriptive analysis which was assessed in the form of a Likert scale. Result: The development of pocket comics media (komiku) on the prevention of dental caries is very feasible to use. Based on media validation by media experts with a proportion of 87.4%, and by material experts with a percentage of 83.3%, it was declared very feasible. In the results of trials involving students, the percentage is 97% and is said to be very feasible. Conclusion: The pocket comic media about the prevention of dental caries that has been developed is said to be very feasible in learning based on the results of student assessments at SD in Padasuka, Central Cimahi District.